DALIHAN NATOLU DAN TRADISI MARGONDANG DALAM PERKAWINAN DI BATAK ANGKOLA - Nada Putri Rohana (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
Marriage is a crucial thing in the marriage section, this is often considered urgent for every family. Marriage underlies two sides in its implementation, namely between religion and custom. Angkola Batak is one of the regions in Indonesia that has specialties in terms of tradition or culture in carrying out marriages that involve the social system of society and culture. The results of the study indicate that the social system of society that begins with the marriage bond gives rise to a dynamic position or position in the family sphere. This also makes this social system intact and strong to maintain the integrity of a marriage. In addition, the cultural values that exist in the tradition also have a good influence on maintaining the diversity that can be taken from the values that exist in its implementation.